Inovasi Teknologi dan Keberlanjutan dalam Menajemen Perubahan Pendidikan - Febrinal, Dian; Saputra, Septia Irnanda; Irawadi, Hermen; Fazis, Muhammad; Roza, Melia (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to identify the technological innovations implemented at SMPN 2 Sijunjung, analyze their impact on the sustainability of education, and evaluate the change management strategies used in the process of technology adaptation. The research method employs a mixed methods approach with a quantitative dominance, involving a purposive sample of 50 teachers and 100 students. Data were collected through surveys, in-depth interviews, and document analysis, then analyzed using descriptive statistics and thematic analysis. The results show that the use of digital platforms such as Google Classroom, Zoom, Kahoot!, and Quizizz increases students’ motivation and engagement in learning. Technical constraints such as limited internet access and devices remain significant barriers. Training and change management support technology adaptation, but communication and stakeholder participation need strengthening to ensure the sustainability of innovations. This study recommends improving infrastructure, teacher training, and developing inclusive policies as efforts to strengthen the sustainability of educational technology